(untitled) (Indian Journal of Animal Production and Management, 2025)
This article examines the contribution of the SCOPUS indexed Indian Journal of Animal Sciences from the SCOPUS database covering the period 2010 to 2024, resulting in 4121 documents. The research emphasizes trends, significant research domains, and the journal’s influence on promoting studies in multidisciplinary fields. The study evaluates publication counts, authorship trends, collaborative patterns among authors, yearly article distribution, and categorization of papers by professional category using various tools and techniques. The analysis shows increasing acknowledgment of the journal’s contributions, highlighting its importance in sharing essential research results. It presents the Indian Journal of Animal Sciences as an important platform to enhance the quality and standards of education and research output and offers potential future research directions in this rapidly developing field.